Assessing and Managing Risk for Cardiovascular Disease: A Worldwide Perspective - Kuklina, MD, PhD, Elena V (North American Journal of Medicine and Science, 2010)
Cardiovascular disease (CVD) has become increasingly recognized as a major cause of disability, premature death, and escalating health-care costs throughout the world. The purpose of the present report is to review the most widely used worldwide tools for assessment of the total (absolute, global, integrated) risk of developing CVD during the next 5 or 10 years and to review guidelines for the clinical management of dyslipidemia, hypertension, and dysglycemia that incorporate these tools. The World Health Organization (WHO) / International Society of Hypertension (ISH) risk charts, The Framingham system, Systematic Coronary Risk Evaluation (SCORE) charts, and the PROCAM (PROspective Cardiovascular Munster) Quick Check and Health Check systems are described. Since the use of clinical guidelines based on these tools has some limitations and challenges, alternative or modified approaches for the management of CVD risk factors have been proposed by several researchers recently. Future studies are needed to evaluate the effectiveness of these proposed strategies